The spectrum of polyneuropathies in patients infected with HIV. Issue 12 (December 1989) - Leger, J M; Bouche, P; Bolgert, F; Chaunu, M P; Rosenheim, M; Cathala, H P; Gentilini, M; Hauw, J J; Brunet, P
Abstract : Twenty five patients with peripheral neuropathy at different stages of human immunodeficiency virus (HIV) infection are reported. Cerebrospinal fluid (CSF) findings were available in 17 cases, electrophysiology in all and a neuromuscular biopsy in 11. Of six otherwise asymptomatic HIV+ patients, five had chronic inflammatory demyelinating polyneuropathy (CIDP) and one acute inflammatory demyelinating polyneuropathy (AIDP). CSF showed pleocytosis in all cases. Infiltration of the endoneurium and/or the epineurium by mononuclear cells was seen in biopsies from three cases. These six patients recovered either spontaneously, or with corticosteroids or plasmaphereses. Of five patients with AIDS related complex (ARC), three had distal predominantly sensory peripheral neuropathy (DSPN), one CIDP and one mixed neuropathy. Of 14 patients with AIDS, one had mononeuropathy multiplex and 13 painful DSPN. Electrophysiological studies were consistent with an axonopathy. Nerve biopsies in six cases showed axonal changes but surprisingly associated with marked segmental demyelination in two cases. Cell infiltration was present in nerve samples in two cases. Five patients died within six months after the onset of the neuropathy.